Exploring the antimicrobial, anti-inflammatory, antioxidant, and immunomodulatory properties of Chrysanthemum morifolium and Chrysanthemum indicum: a narrow review - Yuqing Liang; Tengwen Liu; Dong Wang; Qingquan Liu; Qingquan Liu; Qingquan Liu (Frontiers in Pharmacology)
Infectious diseases continue to be a major global public health concern, which is exacerbated by the increasing prevalence of antimicrobial resistance. This review investigates the potential of herbal medicine, particularly Chrysanthemum morifolium (CM) and Chrysanthemum indicum (CI), in addressing these challenges. Both herbs, documented in traditional Chinese medicine (TCM) and the Pharmacopoeia of the People’s Republic of China (2020 edition), are renowned for their heat-clearing and detoxifying properties. Phytochemical studies reveal that these botanicals contain diverse bioactive compounds, including flavonoids, terpenoids, and phenylpropanoids, which exhibit antimicrobial, anti-inflammatory, and antioxidant properties, among other effects. Comparative analysis reveals that distinct compound profiles and differential concentrations of core phytochemicals between CM and CI may lead to differentiated therapeutic advantages in anti-infective applications. By systematically examining their ethnopharmacological origins, phytochemical fingerprints, and pharmacological mechanisms, this review highlights their synergistic potential with conventional antimicrobial therapies through multi-target mechanisms, proposing novel integrative approaches for global health challenges.